Analysis of English Teachers’ Assessment Strategies Within a Differentiated Learning Context in EFL at SMP Negeri 4 Singaraja - Putri, Kadek Sania Dwiyanti; Wahyuni, Luh Gede Eka; Paramartha, Anak Agung Gede Yudha (Lexeme : Journal of Linguistics and Applied Linguistics, 2026)
This study aimed to analyze English teachers’ assessment strategies within a differentiated learning context and to identify the challenges encountered in implementing differentiated assessment in EFL classrooms. A qualitative research design was employed at SMP Negeri 4 Singaraja, involving three English teachers from different grade levels. Data were collected through classroom observations and unstructured interviews and analyzed using an interactive qualitative data analysis model consisting of data reduction, data display, and conclusion drawing. The findings revealed that teachers applied five main assessment strategies: gamification, reading assignments, writing tasks, speaking performances, and storytelling activities. These strategies predominantly reflected assessment for learning and assessment of learning, while assessment as learning was not observed. Differentiated learning was evident in instructional processes and products; however, assessment criteria were frequently applied uniformly across students. Differentiated assessment was consistently implemented only in speaking performance and storytelling activities, where assessment criteria were adjusted to students’ ability levels. The study also identified several challenges that hindered the implementation of differentiated assessment, including large class sizes, limited instructional time, and teachers’ limited understanding of differentiated assessment concepts. Overall, the findings indicate a partial alignment between differentiated learning and assessment practices, highlighting the need for improved assessment literacy and structural support to enhance equitable assessment in EFL classrooms. In order to manage large classes and provide the best possible individual attention, teachers can first think about flexible grouping tactics or peer tutoring. Also, effective time management and preparation are essential.